THE INFLUENCE OF SECURITY CHECK POINT (SCP) 1 AGAINST PASSENGER SATISFACTION - Ahmad Nugraha, Nandi; Agus Furyanto, Faoyan; Olieve, Arnaz (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Padang Minangkabau International Airport is located in West Sumatra, more precisely in Pariaman Regency. This airport has several terminals namely Domestic Terminal, International Terminal, VIP Terminal, and Cargo Terminal. At the domestic terminal at Minangkabau Airport there are problems that arise, namely the security inspection process that has not used the baggage handling system with and passenger responses. This article examines the effect of the existing security check process on the satisfaction of using the flight services that passengers get. This research utilizes a correlational Technique using a quantitative tactic which collects information derived from monitoring data, distribution of questionnaires, and literature studies. Respondents from this questionnaire are passengers who use flight services and the results of these answers are calculated using the SPSS application. The results of these calculations show that the safety check process or variable X is correlated with passenger satisfaction or variable Y. It is apparent in the correlational test, demonstrating a result of 0.00 which is beneath 0.05, signifying a correlation between the variables. Things that need to be updated at Padang Minangkabau International Airport are the security inspection process in accordance with applicable standard operating procedures and paying more attention to passenger satisfaction in providing services.